Multiple resistance to anthelmintics by Haemonchus contortus and Trichostrongylus colubriformis in sheep in Brazil - Almeida, F. A. [UNESP]; Garcia, K. C. O. D. [UNESP]; Torgerson, P. R.; Amarante, Alessandro Francisco Talamini do [UNESP] (Elsevier B.V., 2010)
The objective of this study was to determine the level of resistance of Haemonchus contortus and Trichostrongylus colubriformis in sheep to levamisole albendazole ivermectin moxidectin closantel and trichlorfon The parasites were isolated from sheep naturally infected by gastrointestinal nematodes and were then kept in monospecifically infected lambs for production of infective larvae (L3) of both species Forty-two lambs at three months of age were simultaneously artificially infected with 4000 L3 of H contortus and 4000 L3 of T colubriformis The animals were allocated Into seven groups with six animals each that received one of the following treatments Group 1-control no treatment Group 2-moxidectin (0 2 mg/kg body weight (BW)) Group 3-closantel (10 mg/kg BW) Group 4-trichlorfon (100 mg/kg BW) Group 5-levamisole phosphate (4 7 mg/kg BW) Group 6-albendazole (5 0 mg/kg BW) and Group 7-ivermectin (0 2 mg/kg BW) Nematode fecal egg counts (FEC) were carried out on the day of treatment and again at 3 7 10 and 14 days post-treatment on the same occasions composite fecal cultures were prepared for each group for production of L3 which were identified into genus The animals were sacrificed for worm counts at 14 days after treatment The efficacy of each treatment was calculated from the arithmetic mean of the FEC or worm burden of the treated group compared with the values of the control group Only trichlorfon and moxidectin treatments resulted in a significant reduction of H contortus recorded at necropsy (73% and 45% respectively) Moxidectin reduced T colubriformis worm burdens by 82% and albendazole by 19% All other anthelmintics resulted in no significant reduction in the numbers of worms found at necropsy In conclusion the Isolates of H contortus and T colubriformis showed multiple resistance to all groups of anthelmintics tested This is the first report based on the controlled efficacy test to show resistance of T colubriformis to macrocyclic lactones in Brazil (C) 2010 Elsevier B.V. All rights reserved
Keywords: Albendazole; Closantel; Ivermectin; Levamisole; Moxidectin; Trichlorfon